UJI MUTU BENIH JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) PADA BERBAGAI CARA EKSTRAKSI BENIH - Arifin, .; Wardah, .; Irmasari, . (Jurnal Warta Rimba, 2018)
Red Jabon is one tree species with high prospects for forest plantation and reforestation plants in Indonesia and expected to meet the demand for wood in the domestic and international markets. Extraction of seeds is one way to maintain seeds quality red Jabon (Anthocephalus macrophyllus (Roxb.) Havil). The use of calcium oxide (Ca(OH)2) which contains the elements calcium (Ca) is one way of extracting the seeds that need to be applied to the Jabon seeds protected by the flesh. This study aims to determine seeds quality of red Jabon on various methods of extractions of seeds so as to obtain an appropriate extraction method to maintain seeds quality of red Jabon. This study uses a completely randomized design (CRD) consisting of four (4) treatment that E0 (without treatment extraction), E1 (extraction dried by sun-drying for two days), E2 (extraction wet by soaking for 24 hours) and E3 (extraction soaking with lime solution 20 g/l for 25 minutes). Each treatment repeated 4 times, so there are 16 experimental units. The parameters measured were the percentage of pure seed, the percentage of moisture content, weight of 1000 grain seeds, germination, the peak value, the average value of daily germination and the value of germination. The results showed that the extraction treatment E3 able to improve the physical quality of seeds plants red Jabon high of 0,021 grams (weight of 1000 grains), 75.886% (purity), 24.114% (dirt seeds) and 5.117% (moisture). E3 extraction treatment was also able to increase seeds viability red Jabon best is 52.2% (germination), 0.508% /day (peak value of germination), 1.74% /day (daily germination value), and 0.885% /day ( the value of germination).Keywords: Anthocephalus macrophyllus (Roxb.) Havil, calcium oxide, seeds quality